2023
DOI: 10.1161/circulationaha.123.064170
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Hematopoiesis in Clinical and Experimental Heart Failure With Preserved Ejection Fraction

Jesse D. Cochran,
Yoshimitsu Yura,
Mark C. Thel
et al.

Abstract: BACKGROUND: Clonal hematopoiesis (CH), which results from an array of nonmalignant driver gene mutations, can lead to altered immune cell function and chronic disease, and has been associated with worse outcomes in patients with heart failure (HF) with reduced ejection fraction. However, the role of CH in the prognosis of HF with preserved ejection fraction (HFpEF) has been understudied. This study aimed to characterize CH in patients with HFpEF and elucidate its causal role in a murine model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Third, while this study benefited from the inclusion of racially diverse cohorts, certain demographic groups were still not represented. However, recent case-control studies that mainly involved participants with demographics different from those in the present study (eg, White male participants) found consistent associations between CHIP or TET2 CHIP and HFpEF, suggesting that our findings may generalize to other demographic groups. Fourth, while WGS enables large-scale genetic analyses in population-based cohorts, it has limited sensitivity to detect CHIP with VAF less than 10% .…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Third, while this study benefited from the inclusion of racially diverse cohorts, certain demographic groups were still not represented. However, recent case-control studies that mainly involved participants with demographics different from those in the present study (eg, White male participants) found consistent associations between CHIP or TET2 CHIP and HFpEF, suggesting that our findings may generalize to other demographic groups. Fourth, while WGS enables large-scale genetic analyses in population-based cohorts, it has limited sensitivity to detect CHIP with VAF less than 10% .…”
Section: Discussionsupporting
confidence: 86%
“…CHIP had increased diastolic dysfunction, ventricular hypertrophy, and cardiac fibrosis in comparison with control mice. 23 Our results corroborate and extend these findings by showing that TET2 CHIP was associated with incident HFpEF in a population-based sample, identifying TET2 CHIP as a strong and independent risk factor for new-onset HFpEF. Additional work using targeted sequencing is needed to determine an optimal VAF threshold for the prognostic significance of TET2-driven clonal hematopoiesis in HFpEF and to define pragmatic approaches for incorporating CHIP as a clinical risk factor for HFpEF.…”
Section: Jama Network Open | Cardiologysupporting
confidence: 88%
See 3 more Smart Citations